ADAPTASI DAN PERENCANAAN PRODUKSI ALAT PELINDUNG DIRI PADA MASA PANDEMI COVID-19 MENGGUNAKAN LEARNING CURVE MODELS - Nuris Maulina Ulfah; Eko Ruddy Cahyadi (School of Business, Bogor Agricultural University (SB-IPB), 2021)
The demand for hazmat suits and masks is increasing due to the Covid-19 Pandemic. To meet the demand, the Government is encouraging SMEs engaged in convection to produce hazmat suits and masks. The purpose of this study is to analyze the adaptation process and the application of aggregate planning as well as provide recommendations for strategies that can be applied based on the production of hazmat suits and masks from February to May 2020 at CV Bangkit Jaya as a convection UKM. The data used in this study were obtained from companies through interviews, company data, and literature studies. Processing and data analysis using learning curves and trial-and-error methods of aggregate planning. The results of this study are the percentage level of the learning curve in adapting to the production of hazmat suits of 96.07 percent and masks of 99.17 percent. Then, Chase Strategy is a scenario with a minimum total cost of Rp 98 834 200. Then, the strategy to control the number of workers was most appropriate for CV Bangkit Jaya in producing hazmat suits and masks. Keywords: adaptation, hazmat suits, masks, production planning strategy, SMEs